Simulation of activated sludge treatment using ASIM 1 version 3.0 with extant kinetic biodegradation parameters - Torres, Wilma S. (2001)
These parameter estimates were used along with process information to generate simulations into the ASIM ver. 3.0 software. Actual influent COD values from facility records were also inputted. Chi-square (X²) tests were run at a confidence level of α =0.05. The simulation runs were successful in predicting effluent COD values if influent conditions were within 75% of the typical influent COD. However, simulations generated using influent COD values more than 75% of typical influent COD were observed to have significant discrepancies between the predicted and actual COD values. Further studies are recommended on how ASIM can model the impact of shock load variations on enffluent COD. The assumption of Monod kinetics may need to be re-evaluated for high COD concentrations, which inhibit biodegradation. Finally, sampling techniques may need to be redefined to provide a better basis for simulation comparisons.
Experimental determination of extant biodegradation kinetic parameters maximum growth rate û (hr-1) the and half-saturation constant Kѕ (mg/L) was conducted through respirometry using activated sludge as biomass and wastewater as substrate taken from an existing activated sludge plant. The wastewater is generated from the process washings of consumer products formulated from sufjonated/sulfated surfactants and contains only a minimal amount of phosphates (0.07%) and no nitrogen-based compounds
Values determined for the maximum growth rate û ranged from 0.360± 0.018 hr-1 to 1.188± 0.036 hr-1, with 95% confidence intervals. values determined for the half-saturation constant Kѕ ranged from 6.8± 0.4 to 8.2 mg/L with 95% confidence inter
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Sewage -- Purification -- Activated sludge process -- Philipp; Sewage disposal plants -- Philipp